Efficacy and safety of Chinese medicine combined with acupuncture in the treatment of chronic urticaria: A meta-analysis. Issue 36 (9th September 2022) - Lu, Zhenxiong; Zhou, Qiujun; Chai, Shiqian; Yang, Huifeng; Wang, Jinhui; Luo, Hongbin; Cao, Yi; Tao, Maocan
Abstract : Background: Increasing studies have shown that Chinese medicine combined with acupuncture has a significant effect on chronic urticaria, which can treat both symptoms and root causes. This meta-analysis aims to compare the efficacy and safety differences between acupuncture combined with conventional Western medicine, so as to provide guidance for the clinical treatment of chronic urticaria. Methods: We searched Pubmed, Embase, Cochrane Library, CNKI, Wanfang, CQVIP, and CBM from the establishment of the database to August 2021. We included randomized controlled trial study that the experimental group was acupuncture combined with traditional Chinese medicine, while the control group was treated with conventional Western medicine. We excluded repeated publication, researches without full text, incomplete information, or inability to conduct data extraction and animal experiments, reviews, and systematic reviews. STATA 15.1 was used to analyze the data. Results: The pooled results show that total effective rate of acupuncture combined with traditional Chinese medicine group was significantly higher than that in the conventional Western medicine group (ratio rate [RR] = 1.29, 95% confidence interval [CI]: 1.2–1.38). Additionally, the pooled results show that Urticaria Activity Score (standardized mean difference = –1.51, 95% CI: –2.24 to –0.78) and pruritus score (standardized mean difference = –1.09, 95% CI: –1.71 to –0.47) of acupuncture combined with traditional Chinese medicine group was significantly lower than that in conventional Western medicine group, while there is no significant difference in wheal score between acupuncture combined with traditional Chinese medicine group and conventional Western medicine group. Importantly, the pooled results show that recurrence rate (RR = 0.35, 95% CI: 0.19–0.64) and the incidence of adverse events (RR = 0.27, 95% CI: 0.10–0.75) of acupuncture combined with traditional Chinese medicine group were all significantly lower than that in conventional Western medicine group. Conclusion: Our research results found that traditional Chinese medicine combined with acupuncture has a more significant effect than conventional Western medicine and can significantly reduce the recurrence rate and the incidence of adverse reactions. The application of traditional Chinese medicine combined with acupuncture in the treatment of chronic urticaria should be further promoted.